Monro-Kellie 2.0: The dynamic vascular and venous pathophysiological components of intracranial pressure. Issue 8 (August 2016) - Wilson, Mark H
For 200 years, the 'closed box' analogy of intracranial pressure (ICP) has underpinned neurosurgery and neuro-critical care. Cushing conceptualised the Monro-Kellie doctrine stating that a change in blood, brain or CSF volume resulted in reciprocal changes in one or both of the other two. When not possible, attempts to increase a volume further increase ICP. On this doctrine's "truth or relative untruth" depends many of the critical procedures in the surgery of the central nervous system. However, each volume component may not deserve the equal weighting this static concept implies. The slow production of CSF (0.35 ml/min) is dwarfed by the dynamic blood in and outflow (∼700 ml/min). Neuro-critical care practice focusing on arterial and ICP regulation has been questioned. Failure of venous efferent flow to precisely match arterial afferent flow will yield immediate and dramatic changes in intracranial blood volume and pressure. Interpreting ICP without interrogating its core drivers may be misleading. Multiple clinical conditions and the cerebral effects of altitude and microgravity relate to imbalances in this dynamic rather than ICP per se. This article reviews the Monro-Kellie doctrine, categorises venous outflow limitation conditions, relates physiological mechanisms to clinical conditions and suggests specific management options.